STOSUNEK WŁADZ BAWARII DO MNIEJSZOŚCI MUZUŁMAŃSKICH - Pisarek, Joanna (Studia Oecumenica, 2014)
In the first part of the article the author pays a lot of attention to the law regulations concerning the religious freedom of the Muslim minorities living on the territory of Federal Republic of Germany. The author shows the way the German legal system determines the scope of a Muslim religion, which finds the new interpretations enabling it to integrate in the inalienable law orders and that the religious freedom guaranteed in the constitution is not unlimited. Thereby, the legal multiculturalism in this important sphere does not exist. The author also describes the process of creating the „parallel“ system of justice, which causes some problems to the German Themis. In the second part of the article the author focuses on the long-standing „Support and require“ integration policy of the Bavarian government and notices that this policy assumes the extensive help and support, which are the constant aim simplifying the process of integration. The author indicates that this policy has to base on the mutuality principle and the measure of its success is the respect for the christian values and the will to integrate. The author also concentrates on the issues caused by the mosques and their function in the integration process.